Leaf characters of Lavoisiera, Microlicia and Trembleya (Microlicieae, Melastomataceae) and their implications for taxonomy - Silva, Kleber Resende [UNESP]; Romero, Rosana; Simão, Daniela Guimarães (Wiley, 2018)
In Microlicieae taxonomical delimitation of Lavoisiera, Microlicia and Trembleya is problematic. This study aims to fill this gap by identifying leaf characters that are useful for taxonomy of these genera. Species of Rhynchanthera were also included in this study for comparison, since it is an early-diverging genus of the tribe. Diagnostic characters of Lavoisiera include sessile leaves with spongy parenchyma composed of isodiametric cells, and acute margins with supporting tissue. Trembleya is distinguished by petiolate, microphyllous, and hypostomatic leaves. The presence of depressions on the leaf surface and a homogeneous mesophyll is observed only in species of Microlicia. The leaf characters observed in Rhynchanthera, together with the available phylogenetic studies, were important to indicate evolutionary tendencies in the leaf structure within Microlicieae. Thus, our results indicate a tendency for reduction in leaf size within the tribe, in relation to both the petiole and the lamina. This reduction, which is more pronounced in Microlicia, results in a greater anatomical heterogeneity, due to variations in the organization of both vascular and fundamental tissues.
Keywords: campo rupestre; leaf anatomy; Myrtales; Rhynchanthera